Hubungan Tingkat Pengetahuan Dengan Perawatan Akses Vaskular Pada Pasien Hemodialisa di Rumah Sakit X - Ernauli Meliyana; Endah Rinukti (STIKes Medistra Indonesia, 2026)
Hemodialysis is a medical procedure used to remove metabolic waste substances, including dissolved substances and water, from the blood through a semi-permeable membrane. Hemodialysis requires good vascular access and vascular access that lasts longer with minimal complications. Central Venous Catheter (CVC), Arteriovenous Fistula (AVF), and Arteriovenous Graft (AVG) are types of vascular access that can be used in patients with kidney failure. Hemodialysis patients need vascular access to maintain hemodialysis. One of the accesses used for hemodialysis patients undergoing routine HD is using an arteriovenous (AVF) often called an AV-shunt. AV-shunt is an access that is commonly used because it has the advantage and convenience of carrying out long-term hemodialysis and fewer complications that occur such as thrombus, infection, bleeding.